V. I. Nilov is “a very modest man and an exceptionally serious scientist” (concerning one comment in M. Gorky’s letter to I. V. Stalin) - A. G. Plotnikova (Труды по прикладной ботанике, генетике и селекции, 2020)
This publication explores the history of personal contacts and correspondence between the distinguished biochemist V. I. Nilov and the writer Maxim Gorky in 1933–1936. Through out his life, M. Gorky tried to use his influence to help talented scientists as well as scientific and cultural institutions. In 1933, V. I. Nilov, a researcher from the Nikita Botanical Gardens, wrote to Gorky about the experiments he performed in his biochemistry lab on the synthesis of vitamin C, plant breeding for chemical composition, and isolation of opiates from poppy. The writer appealed to the USSR top officials, intending to improve the situation with scientific institutions in Crimea. As a result of Gorky’s mediation efforts, Nilov’s documents were presented to I. V. Stalin. The leaders of the USSR were interested in such research, because it complied with the country’s strategic objectives. This, in its turn, led to changes in vitamin research and production in the USSR and had an effect on the status of the Nikita Botanical Gardens. V. I. Nilov’s scientific biography was closely interlinked with the history of the Institute of Plant Industry and its director N. I. Vavilov. By this publication, earlier unknown materials from the Archive of A.M. Gorky (Institute of World Literature, Moscow) and the Russian State Archive of Socio-Political History (Moscow) are for the first time introduced into public scientific discourse.